Making global policy - Stone, Diane, 1964- (Cambridge University Press, 2020)
Global policy making is taking shape in a wide range of public sector activities managed by transnational policy communities. Public policy scholars have long recognised the impact of globalisation on the industrialised knowledge economies of OECD states, as well as on social and economic policy challenges faced by developing and transition states. But the focus has been on domestic politics and policy. Today, policy studies literature is building new concepts of 'transnational public-private partnership', 'trans-governmentalism' and 'science diplomacy' to account for rapid growth of global policy networks and informal international organisations delivering public goods and services. This Element goes beyond traditional texts which focus on public policy as an activity of states to outline how global policy making has driven many global and regional transformations over the past quarter-century. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 22 Nov 2019).
Keywords: Political planning; Public administration -- International cooperation